Analysis of Students' Critical Thinking Skills in Solving Trigonometric Problems - Roland Sianturi; Putri Astrilia (Indo-MathEdu Intellectuals Journal, 2021)
The thought processes practiced in school are limited to cognition, memory, and convergent thinking, while divergent thinking and evaluation are less noticed. Learning activities focused on recording, memorizing, and recalling, learning is concentrated on exercises that are procedural and mechanistic. This research aims to find out the critical thinking skills of students in solving trigonometric problems in grade XI of SMA Negeri 6 Medan. The type of research used is qualitative descriptive. The subjects in this study amounted to 1 person who was selected using the purposive sampling technique, which is the highest score of student test results. The instruments used are tests to find out the student's learning results as the basis for subject selection and interviews are used to find out the student's critical thinking skills. Data analysis used is qualitative data analysis consisting of data reduction, data presentation, and conclusion withdrawal. The results of data analysis obtained that the subject in the learning process and the process of solving the problem of trigonometric material has the ability to think critically. Subjects have three indicators of critical thinking skills used in this study, namely trying to know information well, providing reasons for problem solving, and looking for alternative solutions